Higher intensity of 72‐h noninvasive cardiac test referral does not improve short‐term outcomes among emergency department patients with chest pain. (23rd February 2022) - Mark, Dustin G.; Shan, Judy; Huang, Jie; Ballard, Dustin W.; Vinson, David R.; Kene, Mamata V.; Sax, Dana R.; Rauchwerger, Adina S.; Reed, Mary E.; ,
Abstract: Background: It is unclear whether referral for cardiac noninvasive testing (NIT) following emergency department (ED) chest pain encounters improves short‐term outcomes. Methods: This was a retrospective cohort study of patients presenting with chest pain, without ST‐elevation myocardial infarction or myocardial injury by serum troponin testing, between 2013 and 2019 to 21 EDs within an integrated health care system. We examined the association between NIT referral (within 72 h of the ED encounter) and a primary outcome of 60‐day major adverse cardiac events (MACE). Secondary outcomes were 60‐day MACE without coronary revascularization (MACE‐CR) and 60‐day all‐cause mortality. To account for confounding by indication for NIT, we grouped patient encounters into ranked tertiles of NIT referral intensity based on the likelihood of 72‐h NIT referral associated with the initially assigned emergency physician, relative to local peers and within discrete time periods. Associations between NIT referral‐intensity tertile and outcomes were assessed using risk‐adjusted multivariable logistic regression. Results: Among 210, 948 eligible patient encounters, 72‐h NIT referral frequency was 11.9%, 18.3%, and 25.9% in low, intermediate, and high NIT referral‐intensity encounters, respectively. Compared with the low referral‐intensity tertile, there was a higher risk of 60‐day MACE within the high referral‐intensity tertile (odds ratio [OR] = 1.11, 95% confidence interval [CI] = 1.04 to 1.17) due to more coronary revascularizations without corresponding differences in MACE‐CR or all‐cause mortality. In analyses stratified by patients' estimated risk (HEART score; 50.5% lower risk, 38.7% moderate risk, 10.8% higher risk), the difference in 60‐day MACE was primarily attributable to moderate‐risk encounters (OR = 1.15, 95% CI = 1.08 to 1.24), with no differences among either lower‐ (OR = 1.10, 95% CI = 0.92 to 1.31) or higher‐ (OR = 1.01, 95% CI = 0.90 to 1.14) risk encounters. Conclusion: Higher referral intensity for 72‐h NIT was associated with higher risk of coronary revascularization but no difference in adverse events within 60 days. These findings further call into question the urgency of NIT among ED patients without objective evidence of myocardial injury.